28‐2: Distinguished Paper: Toward Sub‐micron Oxide Thin‐Film Transistors for Digital Holography. Issue 1 (2nd June 2017) - Choi, Ji Hun; Pi, Jae-Eun; Hwang, Chi-Young; Yang, Jong-Heon; Kim, Gi Heon; Kim, Yong-Hae; Kim, Hee-Ok; Kwon, Oh-Sang; Park, Eun-Suk; Hwang, Chi-Sun
Abstract : We fabricated high performance 2‐µm‐channel oxide thin‐film transistors (TFT) on glass substrate for 7‐μm‐pixel‐pitch spatial light modulator (SLM) panel for digital holographic applications. Furthermore, we succeeded in the demonstration of the sub‐micron TFTs, which is an inevitable route to the next‐generation spatial light modulation devices with near 1‐μm pixel pitch.